1996
DOI: 10.1016/0014-5793(96)00993-3
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Gln280 by His in TM6 of the human ORL1 receptor increases affinity but reduces intrinsic activity of opioids

Abstract: The ORLI O(.Opioid Receptor-Like) receptor is the G[10], a heptadecapeptide structurally related, however disprotein-coupled receptor whose amino acid sequence is closest to tantly, to the opioid peptide dynorphin A. In recombinant those of opioid receptors. Residues that are conserved in ORL1CHO cells expressing it, the ORLI receptor mediates inhibiand the three types of opioid receptor, but also a residue, His in tion of adenylyl cyclase not only by nociceptin (which is not the sixth putative transmembrane (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 25 publications
3
45
0
Order By: Relevance
“…Mutation of the following NOP receptor residues to their corresponding conserved opioid receptor residues (A216 5.39 to K, V279 6.51 -Q280 6.52 -V281 6.53 to I-H-I and T305 7.39 to I) confers a functional opioid alkaloid binding site in NOP receptors, which binds opioid antagonists with high affinity, without adversely affecting N/OFQ binding significantly (Meng et al, 1998). This study was consistent with mutagenesis of Q280 in TM6 in NOP to histidine, a TM6 residue conserved in all three opioid receptors, which results in an increase in affinity of opioid agonists lofentanil, etorphine, and NOP Receptor Biology and Function dynorphin A and antagonists diprenorphine and nor-BNI, but does not affect N/OFQ binding or potency significantly (Mollereau et al, 1996b). The effect of the Q280H mutation on the binding of small-molecule NOP receptor ligands is not known; however, a Q280A mutation was shown to reduce the potency of receptor activation by N/OFQ and the NOP agonist SCH 221510 by several orders of magnitude .…”
Section: A Nociceptin Opioid Peptide Receptor Proteinsupporting
confidence: 80%
“…Mutation of the following NOP receptor residues to their corresponding conserved opioid receptor residues (A216 5.39 to K, V279 6.51 -Q280 6.52 -V281 6.53 to I-H-I and T305 7.39 to I) confers a functional opioid alkaloid binding site in NOP receptors, which binds opioid antagonists with high affinity, without adversely affecting N/OFQ binding significantly (Meng et al, 1998). This study was consistent with mutagenesis of Q280 in TM6 in NOP to histidine, a TM6 residue conserved in all three opioid receptors, which results in an increase in affinity of opioid agonists lofentanil, etorphine, and NOP Receptor Biology and Function dynorphin A and antagonists diprenorphine and nor-BNI, but does not affect N/OFQ binding or potency significantly (Mollereau et al, 1996b). The effect of the Q280H mutation on the binding of small-molecule NOP receptor ligands is not known; however, a Q280A mutation was shown to reduce the potency of receptor activation by N/OFQ and the NOP agonist SCH 221510 by several orders of magnitude .…”
Section: A Nociceptin Opioid Peptide Receptor Proteinsupporting
confidence: 80%
“…Saturation-binding analyses have revealed that 4, Meng et al 1996, Mollereau et al 1996, Butour et al 1997, Hashiba et al 2002 and for the rough-skinned newt NOP (K d Z0 . 20 nM; Walthers et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…2; Mouledous et al 2000). Site-directed mutagenesis studies have yielded receptors with both NOP and KOR characteristics (Meng et al 1996, Mollereau et al 1996, Meng et al 1998. Interestingly, in drNOP and other non-mammalian NOPs, some of the amino acids, which are conserved in other NOPs, are replaced by prototypical k residues which are involved in k-ligand recognition (Table 1).…”
mentioning
confidence: 99%
“…1994;Mansour et al, 1997). In addition, gain of function studies with opioid receptor-like ORL1, which is unable to bind opioid ligands, have also demonstrated the importance of the His residue in TM6 for opioid ligkd with His endows ORLl with the ability to bind opioid ligands, including bremazocine (Mollereau et al, 1996;Meng et al, 1996). This important histidine residue is also conserved in both GPR7 (His268) and GPRS (His277).…”
Section: Opioid Receptor-related Pcr Searehmentioning
confidence: 99%
“…A similar approach was conducted with the opioid receptor-like 1. Although ORLl displayed high identity to the opioid receptors (greater than 50% ovenll) it was unable to bind opioid ligands, however, single amino acid replacement experiments demonsfrated that ORLl could be endowed with the ability to bind opioid ligands (Mollereau et al, 1996;Meng et al. 1997;Meng et al, 1998 uses to exclude the binding of opioid ligands, and in addition would help reveal information about the opioid binding pocket in the opioid receptors.…”
Section: Opioid Related Receptors: Gpr7 Gpr8 and Gpr14mentioning
confidence: 99%